Monkey Business Practices on The Selling of “Janda Bolong” Plants in Indonesia: A Review of Islamic Economic Philosophy - Adinugraha, Hendri Hermawan (TAWAZUN: Journal of Sharia Economic Law, 2021)
The sale and purchase of the “Janda Bolong” plant which was busy in the midst of the Covid-19 pandemic at a very fantastic price, which was then suspected to contain monkey business practices. So this study aims to describe a review of the Islamic economic philosophy of monkey business practices in the “Janda Bolong” plants sale and purchase transaction. The research method used is a qualitative research method with the type of library research using a deductive approach. The results of this study indicate that the practice of buying and selling that occurs in the object of the plant “Janda Bolong” is a type of monkey business with objects that are not commonly practiced. The “Janda Bolong” plant sale and purchase transaction contains a fasid (damaged) contract, where the contract is in accordance with the Sharia but in the nature of the contract there is a problem. The price formation process that occurs in it is also unfair, so it is not in accordance with Islamic law. In Islamic economic philosophy, the practice of monkey business in buying and selling the “Janda Bolong” plant is not allowed. Because it denotes the essence of the creation of humans on earth, namely as a caliphate by processing the available resources in order to achieve happiness in this world and the hereafter.